Women’s Empowerment through Farmers' Women’s Groups (KWT): Enhancing Female Productivity in Rural Indonesia - Agung Prajuliyanto (JOSAR (Journal of Students Academic Research), 2025)
This paper examines the role of Kelompok Wanita Tani (KWT), or Women Farmers’ Groups, as a grassroots mechanism for enhancing rural women’s productivity and empowerment in Indonesia. Adopting a qualitative descriptive approach, the study was conducted in three villages in Blitar Regency, East Java, through in-depth interviews, participant observation, and document analysis. The findings demonstrate that KWTs play a pivotal role in increasing women’s household income, strengthening agricultural and entrepreneurial skills, and fostering leadership and community participation. Women involved in KWTs reported greater financial autonomy, confidence in decision-making, and access to local networks. Nonetheless, the study identifies persistent structural challenges such as limited access to capital, inconsistent training support, market dependency, and generational disengagement. To maximize the impact of KWTs, the study recommends integrated interventions that promote institutional support, financial inclusion, digital literacy, and youth participation. This research contributes to the growing discourse on gender, collective action, and rural development in Southeast Asia.